Representation of Women’s Role in Islam on Sermon Content - Zuhriyah, Luluk Fikri; Putriya Hasanah, Eva; Qusnul Qotimah, Rizka (Proceedings of International Conference on Da'wa and Communication, 2022)
This article is motivated by the phenomenon of inequality in the role of women in the public aspect. Seeing da'wah as an essential aspect in influencing the community, the researchers were inspired to understand more deeply the representation of the content of the sermon on the role of women. For academic reasons, the researcher chooses videos from a national women preacher, Oki Setiyana Dewi (OSD), on YouTube. This article uses a qualitative Critical Discourse Analysis (CDA) from Norman Fairclough and social-conflict theory. The results of this research indicate that women in her content sermon consider that women have a significant role in the domestic aspect, including taking care of children and serving their husbands. This is considered a provision from God. Meanwhile, women are allowed to work or play a role in the public sphere but should comply with some provisions. Judging from the theory used, the text of this sermon contains a conflict which is an inequality that limits the role of women. OSD produced the text of this sermon because she understands that women are “aurat” which, if seen by others, will harm them. Besides that, the condition of a patriarchal society also encourages this opinion.